Designing Supplementary Material for the Tenth Grade Students to Learn Descriptive Text - Pebriana, Mirnatalia; Riyanti, Dwi; Rahmani, Eka Fajar (Journal of English Language and Education, 2024)
This research was aimed to design the supplementary material to learn descriptive text for tenth-grade students of SMA Karya Kasih in Parindu, Sanggau, Kalimantan Barat. To conduct this research, the researcher employed RD (Research and Development), which applied the ADDIE procedure, focused on the ADD steps (Analysis, Design and Development). The participants of this research involved an English teacher and 27 tenth-grade students. The researcher distributed online questionnaire to the students and interview the English teacher to collect the data. The result of the analysis of students’ learning needs indicated that most of them wanted the material of descriptive text about tourist destinations. Students also wanted the material of descriptive text about tourists’ destination in their regency area. The result from the interview showed that supplementary material should be aligned with the curriculum and syllabus. During the process of designing and developing, the researcher used Canva application to create the product. Furthermore, the result of the internal validation from the teacher showed that a design of supplementary material was appropriate to use in learning descriptive text.